FROM THE GROUND UP, conversations with Wes Jackson - Keller, Harold W. (Journal of the Botanical Research Institute of Texas, 2024)
The book narrative is a series of five conversations with Wes Jackson. Questions are posed and Jackson answers. The First Conversations is about Intellectual Grounding that focuses on his schooling beginning with a two-room rural school house to his doctorate in genetics. He tries to dispel the notion he is a genius but his thinking about the importance of soil and conservation issues has always been “outside the box.” There is an appreciation of growing up on a farm in rural Topeka, Kansas, and the importance of a work ethic. This topical section is worth reading to appreciate the beauty of the tallgrass prairie landscape in the Flint Hills of Kansas.